Hematological Side Effects of Immune Checkpoint Inhibitors: The Example of Immune-Related Thrombocytopenia - Calvo, Roser (Frontiers in Pharmacology, 2019)
Immune-related hematological adverse events are amongst the rare but potentially life-threatening complications of immune checkpoint inhibitors. The spectrum of these toxicities is broadening as the number of patients exposed to these agents is increasing. Yet, they are still relatively unknown to many clinicians, possibly due to a lack of specific diagnostic criteria, which poses a challenge for their recognition and proper reporting, and partly due to their low incidence, with a frequency threshold often too low to be noted in most clinical trial publications. Since early detection and prompt intervention are crucial to prevent fatal consequences, it is of outmost importance that medical staff and patients be aware of these potential toxicities and learn to recognize and treat them adequately. This publication outlines strategies and offers guidance on the detection, diagnosis, risk assessment, monitoring and management of immune-related thrombocytopenia, a relatively common example of immune-related hematological toxicity of immune checkpoint inhibitors